Integrating filter paper extraction, isothermal amplification, and lateral flow dipstick methods to detect Streptococcus agalactiae in milk within 15 min - Zhu, Lingling; Gong, Fengju; Liu, Xia; Sun, Xueqiang; Yu, Yong; Shu, Jie; Pan, Zihao (Frontiers in Veterinary Science, 2023)
Mastitis is one of the most serious diseases affecting dairy farming, causing huge economic losses worldwide. Streptococcus agalactiae is the main pathogenic bacteria of contagious mastitis and can deliver devastating blows to a farm’s economy. Rapid detection is key to controlling the disease. In this study, a rapid detection method was established for S. agalactiae. The method combines filter paper extraction, multienzyme isothermal rapid amplification (MIRA) and lateral flow dipsticks (LFD). To simplify the extraction procedure, we designed a disposable extraction device (DED). The performance of the DED was first evaluated by PCR, and then the lysis formula and extraction time were optimized. Next, the study compared the extraction performance of the filter paper and the automatic nucleic acid extraction instrument. After screening primers, MIRA for S. agalactiae was established and was combined with LFD. The specificity and sensitivity were evaluated after optimizing the reaction conditions. Results showed that the lowest extraction line of DED was 0.01–0.001 ng/μL. In the specificity study, 12 different bacteria were tested, and only S. agalactiae was positive. In the sensitivity study, seven dilution gradients were established, and the lowest detection line was 3.52×102 CFU/mL. In summary, the method established in this study requires no laboratory equipment and is suitable for on-site detection. The entire method only takes 15 min and is low cost, has a high accuracy, and low technical requirements for operators, which contrasts with the high cost and cumbersome operation of traditional methods, and is adapted to on-site testing in areas with limited facilities.